MAP kinase phosphatase 1 is expressed and enhanced by FK506 in surviving mamillary, but not degenerating nigral neurons following axotomy - Winter, Christine; Schenkel, Johannes; Zimmermann, Manfred; Herdegen, Thomas (Brain research, 1998)
The MAP kinase phosphatase 1 (MKP-1), a dual serine-threonine phosphatase, inactivates the MAP kinases ERK and JNK/SAPK which are involved in neuronal survival and neuronal cell death following injury and degenerative stimuli. We have studied by immunocytochemistry whether regulation of MKP-1 is part of the cell-body response following nerve fiber transection. The expression of MKP-1 was investigated in axotomized neurons of the corpus mamillaris (CMm) and substantia nigra pars compacta (SNC) following transection of the mamillo-thalamic tract (MT) and the medial forebrain bundle (MFB), respectively. In contrast to the surviving CMm neurons, the vast majority of SNC neurons undergoes cell death following axotomy. MKP-1 immunoreactivity which is absent in untreated adult rats, appeared in CMm neurons 24 h following MT transection, reached a maximum after 2 days and persisted in a substantial proportion of CMm neurons until 20 days, the end of observation period. In contradistinction, MKP-1 could not be detected in the SNC neurons. MKP-1 immunoreactivity was virtually restricted to the nuclei of neurons. Subcutaneous injection of the immunosuppressant FK506 that protects axotomized SNC neurons against neuronal cell death, enhanced the expression of MKP-1 in CMm, but failed to do so in SNC neurons. The selective expression of MKP-1 in CMm is the first finding on a different regulation of components in the stress kinase signal pathway in surviving vs. degenerating axotomized neurons.